MAPPING KNOWLEDGE MANAGEMENT DALAM MENINGKATKAN KAPABILITAS PERGURUAN TINGGI - Farid Fauzi (JURNAL AL-TANZIM, 2020)
This study aims to analyze the mapping of several supporting and inhibiting factors of knowledge management process in increasing the higher education capabilities of STAIN Gajah Putih. This study used case study as methodological approach by collecting data with interviews, observation, and documentation. The objects of this study are lecturer, staf and students. The result showed that; 1) The formation of a culture of knowledge sharing; 2) Facilities and infrastructure in supporting the process of knowledge management; 3) Public policy in using knowledge. In establishing capabilities based on the knowledge management process, STAIN Gajah Putih has fixed these deficiencies in terms of the knowledge management process by establishing good information validation, analyzing the needs of knowledge management process, and developing brainware through increasing the quantity and quality of human resources in the field of information technology.